Conserved temporal ordering of promoter activation implicates common mechanisms governing the immediate early response across cell types and stimuli. Issue 8 (8th August 2018) - Vacca, Annalaura; Itoh, Masayoshi; Kawaji, Hideya; Arner, Erik; Lassmann, Timo; Daub, Carsten O.; Carninci, Piero; Forrest, Alistair R. R.; Hayashizaki, Yoshihide; Aitken, Stuart; Semple, Colin A.
Abstract : The promoters of immediate early genes (IEGs) are rapidly activated in response to an external stimulus. These genes, also known as primary response genes, have been identified in a range of cell types, under diverse extracellular signals and using varying experimental protocols. Whereas genomic dissection on a case-by-case basis has not resulted in a comprehensive catalogue of IEGs, a rigorous meta-analysis of eight genome-wide FANTOM5 CAGE (cap analysis of gene expression) time course datasets reveals successive waves of promoter activation in IEGs, recapitulating known relationships between cell types and stimuli: we obtain a set of 57 (42 protein-coding) candidate IEGs possessing promoters that consistently drive a rapid but transient increase in expression over time. These genes show significant enrichment for known IEGs reported previously, pathways associated with the immediate early response, and include a number of non-coding RNAs with roles in proliferation and differentiation. Surprisingly, we also find strong conservation of the ordering of activation for these genes, such that 77 pairwise promoter activation orderings are conserved. Using the leverage of comprehensive CAGE time series data across cell types, we also document the extensive alternative promoter usage by such genes, which is likely to have been a barrier to their discovery until now. The common activation ordering of the core set of early-responding genes we identify may indicate conserved underlying regulatory mechanisms. By contrast, the considerably larger number of transiently activated genes that are specific to each cell type and stimulus illustrates the breadth of the primary response.